English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

prove that sec square of x times cscx divided by sec square of x plus csc square of x equals to sinx

2007-01-28 13:11:06 · 2 answers · asked by zero 1 in Science & Mathematics Mathematics

2 answers

for quick notation let s= sec, s2=sec2, c = csc , c2=csx2

(s2 c) / (s2 + c2) = sin

s2 c = sin (s2 +c2)

(1/cos2) (1/sin) = sin [(1/cos2) + (1/sin2) ] = (sin/cos2) + (1/sin)

multiply both sides by cos

(1/cos) (1/sin) = (sin/cos) + (cos/sin)

1/(cos sin) = (sin/cos) + (cos/sin)

multiply both sides by sinx cosx

1 = sin^2x + cos^2x

1 = 1

2007-01-28 14:11:01 · answer #1 · answered by ignoramus_the_great 7 · 0 0

sec x = 1/sin x and csc x=1/ cos x

sec^2 x / sec^2 x = 1 so the above reduces to

csc x + csc^2 x = sin x not necessarily true.

2007-01-28 21:24:30 · answer #2 · answered by LGuard332 2 · 0 0

fedest.com, questions and answers